Congenital Anterior Urethrocutaneous Fistula with a Persistent Urethral Groove - Hazem Mosa; Massimo Garriboli (Georg Thieme Verlag KG, 2021)
Congenital anterior urethrocutaneous fistula (CAUF) is a rare penile anomaly with only 63 cases reported in the literature. The anomaly can present in isolation or in association with chordee or hypospadias. We report the case of an 8-month-old boy with CAUF that resembles the embryological urethral groove. On examination, a wide urethral groove was noted to cover the midshaft of the penis with a well formed urethra extending proximally and distally and with a normal glandular anatomy, a wide glandular meatus, and a complete foreskin. The urethral groove was tubularized and covered in layers. Surgery was complicated with early superficial skin dehiscence not affecting the urethral repair. Refashioning of the skin was then performed. A satisfactory aesthetic and functional outcome was observed at 7 years' follow-up. Defining the anatomy of CAUF and distal urethra is key in management of these children.